Environmental factors influencing milk yield and lactation length in Italian Mediterranean buffaloes in Türkiye - Yenilmez, K; Dogan, H; Özbaşer, FT (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was conducted to investigate the effects of the environmental factors including, birth season, lactation number, age, and service period, on the annual average lactation milk yield and lactation period of the Italian Mediterranean Buffaloes that were milked by rotary milking systems. The research was carried out on the data of 347 buffaloes in a modern dairy farming between 2016 and 2018 years. Their annual average lactation milk yield and lactation period were found to be 1587.55 ± 33.82 L and 247.66 ± 4.39 days. It was observed that the prolonged service period had a positive effect on the total lactation milk yield and lactation period. The season did not affect the lactation milk yield, but the lactation period was longer in the buffaloes calving in winter months. The service period has a direct effect on the economic profitability, and it was observed that the service periods of buffaloes calving in winter was shorter. It was also determined that milk productivity was positively affected due to the increase in age and lactation number, but there were wide variations in the herd. In conclusion, age, lactation number, and service period were efficient on the annual average milk yield and lactation period, but, on the other hand, the season did not affect the annual average milk yield. More breeding studies are required to minimize variations in buffalo herds milked by different milking techniques.